Estimates of the growth of conjugated harmonic polynomials in the regions of a complex plane - Maimeskul, V. V. (Ukrains’kyi Matematychnyi Zhurnal, 1990)
For an arbitrary Jordan domain G one establishes an estimate of the norm of the operator of harmonic conjugation in spaces of harmonic polynomials of degree at most n, n = 1, 2,….